2016
DOI: 10.1186/s12889-016-3356-7
|View full text |Cite
|
Sign up to set email alerts
|

Reducing violence and increasing condom use in the intimate partnerships of female sex workers: study protocol for Samvedana Plus, a cluster randomised controlled trial in Karnataka state, south India

Abstract: BackgroundFemale sex workers (FSWs) are at increased risk of HIV and STIs compared to women in the general population, and frequently experience violence in their working and domestic lives from a variety of perpetrators, which can enhance this risk. While progress has been made in addressing violence by police and clients, little work has been done to understand and prevent violence by intimate partners (IPs) among FSW populations.MethodsSamvedana Plus is a multi-level intervention programme that works with F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 68 publications
5
28
1
2
Order By: Relevance
“…There are several public health implications of our findings. As also suggested by others (e.g., Beattie et al, 2010;Beattie et al, 2016;Reza-Paul et al, 2012), interventions should take a multifaceted and multilevel approach to addressing violence prevention in the FSW population. One such intervention took place in Andhra Pradesh in 2011-2012 and aimed to reduce work-related violence against FSWs in an HIV prevention context.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…There are several public health implications of our findings. As also suggested by others (e.g., Beattie et al, 2010;Beattie et al, 2016;Reza-Paul et al, 2012), interventions should take a multifaceted and multilevel approach to addressing violence prevention in the FSW population. One such intervention took place in Andhra Pradesh in 2011-2012 and aimed to reduce work-related violence against FSWs in an HIV prevention context.…”
Section: Discussionmentioning
confidence: 91%
“…There was a postintervention reduction in violence, but no control group was available (India HIV/ AIDS Alliance, 2014). A randomized trial evaluating an intervention to reduce violence and increase condom use in FSWs' primary relationships in Karnataka, South India (Beattie et al, 2016), targeted the FSWs (e.g., personal safety plan) and their primary partners (e.g., one-on-one discussions), including couple counseling. It also trained community-based organizations to respond to IPV and aimed to educate the wider community about IPV (e.g., street plays).…”
Section: Discussionmentioning
confidence: 99%
“…All studies had quantitative study designs. Four studies employed a cluster or individual-level randomised controlled trial design 37–40. Five studies used a pre/post design,36 41–45 and one reported baseline data from a pre/post study 46.…”
Section: Resultsmentioning
confidence: 99%
“…Em um estudo internacional de revisão de literatura sobre determinantes da prevalência e incidência 16 . É necessário destacar, que para este presente estudo, o nível de escolaridade não apresentou correlação com o uso de preservativo, ou seja, não interferiu na adesão das mulheres profissionais do sexo à camisinha, o que difere de alguns estudos desenvolvidos no Brasil e no mundo 12,14,[16][17] . Porém, esta característica será percebida em diferentes pesquisas, pois os aspectos da prostituição modificam conforme as localidades e o acesso às políticas públicas de saúde 11 .…”
Section: Discussionunclassified
“…Quanto à associação da vulnerabilidade à infecção do vírus HIV/Aids concernente ao nível de escolaridade e pobreza, estudos têm mostrado que, entre o grupo soropositivo, as mulheres apresentam maior frequência em baixa escolaridade e situação de pobreza [12][13]19,22,26 . Este fato torna os grupos sociais menos favorecidos, inclusive as profissionais do sexo, mais vulneráveis à disseminação do vírus do HIV possivelmente por falta de conhecimento, menor acesso aos meios de prevenção e serviços de saúde, em decorrência do preconceito e estigma por parte dos profissionais de saúde, além da dificuldade em dialogar sobre o uso do preservativo [25][26] .…”
Section: Discussionunclassified